(untitled) (Journal of Partial Differential Equations, 2002)
" The Boussinesq approximation, where the viscosity depends polynomially on the shear rate,finds more and more frequent use in geological practice. In this paper, we consider the periodic initial value problem and initial value problem for this modified Boussinesq approximation with the viscous part of the stress tensor 03c4^v = 03c4(e)- 203bc0394e, where the nonlinear function 03c4(e) satisfies 03c4001c_ij(e)e_ij 2265 C|e|^p or 001c03c4_ij(e)e_ij 2265 C(|e|00b2+|e|^p). The existence, uniqueness and regularity of the weak solution is proved for p > frac2nn + 2."